PEMANFAATAN TEPUNG AMPAS SARI KEDELAI (OKARA) SEBAGAI BAHAN ALTERNATIF PEMBUATAN KUE UNTUK MENGURANGI PENCEMARAN LINGKUNGAN DI KABUPATEN TAPIN PROVINSI KALIMANTAN SELATAN - Febtu Arisandi; Idiannor Mahyudin; Suyanto Suyanto; Emmy Sri Mahreda (Universitas Lambung Mangkurat, 2022)
One of the the soybean extract wastes is a solid waste in the form of soybean extract dregs. This waste can cause a pungent odor due to the fermentation process. Therefore, an action is needed to handle the process so that this waste does not damage the environment; one way is to convert soybean extract waste into dregs flour of soybean extract. Soybean dregs flour (okara) can be used as a substitute for making cake product. This study aims to determine the formulation of ingredients for making cakes, to analyze the level of preference of respondents on all parameters: color, aroma, taste, and texture of cake product, and to assess the efficiency level of utilization of the dregs waste of soybean extract into dregs flour of soybean extract (okara) in cake product made from the substitution of dregs flours of soybean extract (okara). Overall, the acceptance of cake products with a scale value above 3 means that the products is acceptable to the respondents. The efficiency of utilization solid waste from soybean extract processing in the form of soybean extract dregs to become dregs flour of soybean extract (okara) was 60%. Utilization of dregs flour of soybean extract (okara) as an alternative ingredient for making bakery products was able to substitute wheat flour in making cakes by 50%.